2020
DOI: 10.21203/rs.3.rs-28956/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Death Cafes for Prevention of Burnout in Intensive Care Unit Employees: Study Protocol for a Randomized Controlled Trial (STOPTHEBURN)

Abstract: Background: Burnout is an occupational syndrome that leads to mental health problems, job turnover, and patient safety events. Those caring for critically ill patients are especially susceptible due to high patient mortality, long hours, and regular encounters with trauma and ethical issues. Interventions to prevent burnout in this population are needed. Preliminary studies suggest debriefing sessions may reduce burnout. This study aims to assess whether participation in regular debriefing can prevent burnout … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Work alienation refers to the subjective psychological experience in which the material, spiritual and other important needs of individuals cannot be met at work, which leads to the separation of employees from work and negative coping at work (Amarat et al, 2019). The sense of work alienation can easily lead to a decline in nurses' work autonomy (Tummers and Den Dulk, 2013), participation in decision-making (Mudallal et al, 2017), and nursing quality (Jun et al, 2021) and an increase in the turnover rate and nursing safety (Bateman et al, 2020). Especially during the COVID-19 pandemic, the number of nurses had difficulty coping with large-scale infections, and the work pressure increased (Denning et al, 2021).…”
Section: Nurses' Work Alienation and Empathymentioning
confidence: 99%
“…Work alienation refers to the subjective psychological experience in which the material, spiritual and other important needs of individuals cannot be met at work, which leads to the separation of employees from work and negative coping at work (Amarat et al, 2019). The sense of work alienation can easily lead to a decline in nurses' work autonomy (Tummers and Den Dulk, 2013), participation in decision-making (Mudallal et al, 2017), and nursing quality (Jun et al, 2021) and an increase in the turnover rate and nursing safety (Bateman et al, 2020). Especially during the COVID-19 pandemic, the number of nurses had difficulty coping with large-scale infections, and the work pressure increased (Denning et al, 2021).…”
Section: Nurses' Work Alienation and Empathymentioning
confidence: 99%
“…For BOS intervention, there are already reports that some psychological interventions are helpful in nurses. For example, a previous randomized controlled trial (RCT) reported that recording three good things each day significantly improved self-efficacy and job performance in BOS nurses [ 55 ] while an RCT called STOP THE BURN is ongoing to reveal the effect of “death cafés” for preventing BOS in ICU nurses [ 56 ]. The still-new death café concept is a debriefing method focusing on death now being studied for its ability to bring self-efficacy to applicable fields [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, during the pandemic, holding these meetings became more difficult, one possibility pointed out by the authors would be the online format. The authors argue that professionals are quite resistant to accepting the experience, but the professionals who participate report being able to better deal with the questions, insecurities, stress and feelings when they have contact with death 17 .…”
Section: Discussionmentioning
confidence: 99%